مستوى التفكير الاستدلالي المستند إلى حل المشكلة لدى طلبة كلية العلوم التربوية والآداب / الأونروا وعلاقته ببعض المتغيرات - العبسي، محمد مصطفى محمد; استيتي، محمد شريف مصطفى (جامعة الخليل, 2022)
هدفت هذه الدراسة إلى قياس مستوى التفكير الاستدلالي المستند إلى حل المشكلة لدى طلبة كلية العلوم التربوية والآداب/ الأونروا، وعلاقته ببعض المتغيرات. وتكونت عينة الدراسة من (117) طالبا وطالبة، تم تعريضهم لمقياس التفكير الاستدلالي المكون من خمسة مجالات، يتكون كل منها من خمس فقرات، وهذه المجالات هي: تحديد المشكلة، وصياغة الفرضيات، واختبار الفرضيات، والتفسير، والتعميم. وقد أظهرت نتائج الدراسة أن مستوى التفكير الاستدلالي كان متوسطا في المقياس الكلي وفي جميع المجالات، باستثناء مجال التعميم فقد كان مستوى التفكير الاستدلالي مرتفعا. كما أظهرت النتائج وجود فروق ذات دلالة إحصائية في مستوى التفكير الاستدلالي حسب متغير المعدل التراكمي لصالح الطلبة ذوي المعدلات الأعلى مقارنة بذوي المعدلات الأدنى، فيما لم توجد فروق ذات دلالة إحصائية في مستوى التفكير الاستدلالي حسب متغير الكلية. This study aimed to measure the level of evidential thinking based on problem-solving among students of the Faculty of Educational Sciences and Arts/ UNRWA, and its relationship to some variables. The study sample consisted of (117) male and female students, who were administered to the Evidential Thinking Scale containing five subscales, each composed of five items. The five subscales are problem defining, hypotheses formulation, hypotheses test, explaining, and generalization. The results of the study showed that the level of evidential thinking was average on the total scale and on all subscales, except for the generalization subscale, where the level of evidential thinking was high. The results also showed that there are statistically significant differences in the level of evidential thinking according to the cumulative Grade Point Average (GPA) variable, where students with higher GPAs scored significantly higher than those with lower GPAs, while there were no statistically significant differences in the level of evidential thinking according to the faculty variable.
Keywords: طلبة الجامعة -- التفكير الاستنباطي -- التحصيل الأكاديمي -- التفكير العلمي